Comparative study on the performance of TFRC and SCTP over AODV in MANET - Awang Nor, Shahrudin; Dakkak, Omar (Springer India, 2015)
This study aims at comparing study the performance of two transport protocols in MANET environment, which are TFRC and SCTP.Because fairness is one of the features in TFRC, it has attracted real-time applications, whereas multi-homing and multi streaming features in SCTP attracted multimedia applications to use it as a transport protocol instead of TCP and UDP.However, both TFRC and SCTP are facing challenges.The challenge faced by TFRC, which uses additive increase, is to adjust the sending rate during periods with no congestion. This may lead to the short-term congestion that can degrade the quality of voice applications.On the other hand, SCTP faces challenges in the best-effort network.The simulation study was conducted in two scenarios; the first one is with the absence of background traffic, which is single traffic, whereas the second one is in the presence of background traffic, which is non-single traffic.For the simulation, NS-2 simulator was used, the mobility of the nodes was set randomly and the traffic type is CBR.In both scenarios, SCTP has better performance in terms of throughput, whereas TFRC has less delay than SCTP. AODV was chosen as a routing protocol for TFRC and SCTP with throughput and delay as the performance metrics.